Making pragmatic choices: women's experiences of delivery care in Northern Ethiopia - Gebrehiwot Tesfay; Goicolea Isabel; Edin Kerstin; Sebastian Miguel (BMC, 2012)
Abstract Background In 2003, the Ethiopian Ministry of Health launched the Health Extension Programme (HEP), which was intended to increase access to reproductive health care. Despite enormous effort, utilization of maternal health services remains limited, and the reasons for the low utilization of the services offered through the HEP previously have not been explored in depth. This study explores women's experiences and perceptions regarding delivery care in Tigray, a northern region of Ethiopia, and enables us to make suggestions for better implementation of maternal health care services in this setting. Methods We used six focus group discussions with 51 women to explore perceptions and experiences regarding delivery care. The data were analysed by means of grounded theory. Results One core category emerged, 'making pragmatic choices', which connected the categories 'aiming for safer deliveries', 'embedded in tradition', and 'medical knowledge under constrained circumstances'. In this setting, women - aiming for safer deliveries - made choices pragmatically between the two available models of childbirth. On the one hand, choice of home delivery, represented by the category 'embedded in tradition', was related to their faith, the ascendancy of elderly women, the advantages of staying at home and the custom of traditional birth attendants (TBAs). On the other, institutional delivery, represented by the category 'medical knowledge under constrained circumstances', and linked to how women appreciated medical resources and the support of health extension workers (HEWs) but were uncertain about the quality of care, emphasized the barriers to transportation. In Tigray women made choices pragmatically and seemed to not feel any conflict between the two available models, being supported by traditional birth attendants, HEWs and husbands in their decision-making. Representatives of the two models were not as open to collaboration as the women themselves, however. Conclusions Although women did not see any conflict between traditional and institutional maternal care, the gap between the models remained and revealed a need to reconcile differing views among the caregivers. The HEP would benefit from an approach that incorporates all the actors involved in maternal care, at institutional, community and family levels alike. Reconsideration is required of the role of TBAs, and a well-designed, community-inclusive, coordinated and feasible referral system should be maintained.